Coordination, organizations, institutions, and norms in agent systems II : AAMAS 2006 and ECAI 2006, International Workshops, COIN 2006, Hakodate, Japan, May 9, 2006, Riva del Garda, Italy, August 28, 2006 : revised selected papers - COIN; Symposium on Adaptive Agents and Multi-Agent Systems; European Conference on Artificial Intelligence; Noriega, Pablo (Lecture Notes in Computer Science, 2007)
In recent years, social and organizational aspects of agency have become major research topics in MAS. Recent applications of MAS on Web services, grid c- puting and ubiquitous computing highlight the need for using these aspects in order to ensure social order within such environments. Openness, heterogeneity, and scalability of MAS, in turn, pose new demands on traditional MAS int- action models and bring forward the need to look into the environment where agents interact and at di?erent ways of constraining or regulating interactions. Consequently, the view of coordination and governance has been expanding to entertain not only an agent-centric perspective but societal and organizati- centric views as well. The overall problem of analyzing the social, legal, economic, and technolo- caldimensionsofagentorganizations,andthe co-evolutionofagentinteractions, provide theoretically demanding and interdisciplinary research questions at d- ferent levels of abstraction. The MAS research community has addressed these issues from di?erent perspectives that have gradually become more cohesive around the four notions in the title to the workshop: coordination, organization, institutions, and norms. The COIN workshops are thus designed to consolidate the subject by providing focus events that reach researchers from diverse c- munities working in related topics and facilitate more systematic discussion of themes that have been treated from various perspectives. This year, the COIN workshops were hosted during AAMAS 2006, (on June 9,in Hakodate,Japan)and ECAI2006(on August28,in Rivadel Garda,Italy). The papers contained in this volume are the revised versions of a selection of thosethatwerepresented in these workshops.